2009
DOI: 10.1017/s0043887109000148
|View full text |Cite
|
Sign up to set email alerts
|

Ethnonationalist Triads: Assessing the Influence of Kin Groups on Civil Wars

Abstract: Although the case-based literature suggests that kin groups are prominent in ethnonationalist conflicts, quantitative studies of civil war onset have both overaggregated and underaggregated the role of ethnicity, by looking at civil war at the country level instead of among specific groups and by treating individual countries as closed units, ignoring groups' transnational links. In this article the authors integrate transnational links into a dyadic perspective on conflict between marginalized ethnic groups a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
80
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 204 publications
(85 citation statements)
references
References 69 publications
2
80
0
3
Order By: Relevance
“…Ethnic transnational ties are a typical example. Consistently with the argument that ethnic wars produce strong emulation and demonstration effects (Sambanis 2001;Bakke 2013;Weidmann 2015), several papers find that contagion is stronger when ethnic groups are partitioned between a neighbour at war and the domestic country (Cederman, Girardin, and Gleditsch 2009;De Groot 2011;Cederman et al 2013;Bosker and de Ree 2014). The influx of refugees is another form of interaction that should facilitate diffusion.…”
Section: Interaction Opportunitiesmentioning
confidence: 71%
“…Ethnic transnational ties are a typical example. Consistently with the argument that ethnic wars produce strong emulation and demonstration effects (Sambanis 2001;Bakke 2013;Weidmann 2015), several papers find that contagion is stronger when ethnic groups are partitioned between a neighbour at war and the domestic country (Cederman, Girardin, and Gleditsch 2009;De Groot 2011;Cederman et al 2013;Bosker and de Ree 2014). The influx of refugees is another form of interaction that should facilitate diffusion.…”
Section: Interaction Opportunitiesmentioning
confidence: 71%
“…Recently, the rapid rise of the Islamic State of Iraq and the Levant (ISIL) has raised similar concerns about the contagious spread of terrorism across the border of Syria and Iraq into Turkey, Jordan, and elsewhere. 3 While there has been a growing literature on the extent to which civil war, 4 ethno-nationalist conflict, 5 insurgency, 6 and state failure 7 are geographically contagious, there have been a limited number of studies of the different forms of contagion and the extent to which these forms are observed for terrorism. The extant literature on the geography of terrorism is modest and most of the studies that exist focus on the distribution and diffusion of terrorism in specific countries, 8 "hot spots" across countries within regions, 9 regions, 10 or the diffusion of specific terrorist tactics.…”
Section: The Contagious Diffusion Of World-wide Terrorism: Is It Lessmentioning
confidence: 99%
“…5 Furthermore, political activists in one country can obtain sanctuary and support from their transnational kindred, affecting the balance of power and motivation within the country in question (Salehyan 2007, Cederman et al 2009). Thus, the external intervention and the level and kind of external assistance combined with the occurrence of similar rebellions in the region constitute significant causes of intra-state wars (Rwantabagu 2001).…”
Section: External Factorsmentioning
confidence: 99%